SOS: Medien des Überlebens Die existenzielle Bedeutung von Lebenszeichen in Notfällen - Siegler, Martin (Undisziplinierte Bücher, 2023)
SOS signals, knocks, flares, or messages in a bottle: when people find themselves in distress, they must use all possible means to draw attention to themselves. They have to send distress signals in order to stay alive. This book examines numerous catastrophes to show why people in emergencies are existentially dependent on media and means of communication.